Peran BUMDes Dalam Mendukung SDGs di Desa Sindangsari Kecamatan Cikoneng Kabupaten Ciamis - Muhamad Ilham Firdaus; Regi Refian Garis; Asep Nurdin Rosihan Anwar (Papsel Journal of Humanities and Policy, 2024)
Sustainable Development Goals (SDGs) is the government's effort to reduce poverty and improve community welfare. One way to achieve this goal is through the development of Village-Owned Enterprises (BUMDes). BUMDes is a tool to improve the economy and welfare of village communities. The aim of this research is to determine the role of Village-Owned Enterprises in supporting the achievement of the objectives of the Sustainable Development Goals program in Sindangsari Village, Cikoneng District, Ciamis Regency. The method used in this research is descriptive qualitative method. Data was obtained in this research through observation, documentation and interviews with 11 informants, namely the village head, village secretary, BPD chairman, BUMDes director, BUMDes secretary, BUMDes supervisor, and 5 community leaders. The results of the research show that two of the five role indicators according to Siagian have not worked optimally, including the role as a pioneer and as an implementer himself. So it can be concluded that the role of BUMDes Bhinekasari Mandiri in supporting the Sustainable Development Goals (SDGs) has not gone well.   Keywords: Sustainable Development Goals; BUMDes; Role